Prognostic Value and Clinical Predictors of Lymph Node Metastases in Pancreatic Neuroendocrine Tumors. Issue 3 (March 2020) - Zhang, Zheng; Liu, Mengqi; Ji, Shunrong; Luo, Guopei; Xu, Wenyan; Liu, Wensheng; Hu, Qiangsheng; Sun, Qiqing; Ye, Zeng; Qin, Yi; Fan, Guixiong; Yu, Xianjun; et al.
Abstract : Objectives: To investigate the correlation between lymph node metastasis (LNM) and various clinicopathological features of pancreatic neuroendocrine tumors (pNETs) and its impact on prognosis. Methods: We searched the Surveillance Epidemiology and End Results database (2004–2015) for patients with surgically treated pNETs. Factors correlated with LNMs were analyzed by logistic regression and by Cox analysis. Results: For tumors of 1 to 4 cm, age ( P < 0.001, P = 0.014), grade ( P < 0.001, P < 0.001), LNMs ( P = 0.008, P < 0.001), and size ( P = 0.038, P = 0.002) predicted overall survival (OS) and disease-specific survival (DSS). For tumor greater than 4 cm, age ( P < 0.001, P = 0.001) and grade ( P = 0.011, P = 0.048) were independent prognostic factors of OS and DSS. Lymph node metastasis modestly predicted DSS ( P = 0.028) but not OS ( P = 0.218). Conclusions: In pNETs greater than 4 cm, LNM is not a predictor of OS and modestly predicts DSS, and lymphadenectomy may be unhelpful in these patients. For pNETs 1 to 4 cm, LNM predicts poor OS and DSS, which supports lymphadenectomy in these patients. Pancreas-sparing resection with only limited peripancreatic node sampling needs to be questioned.